Rethinking the Security Architecture of North East Asia - Kelly, Michael J; Watts, Sean (Victoria University of Wellington Law Review, 2010)
In the aftermath of the Cold War, many began to question the continuing efficacy, or at least call for reform, of collective security structures such as the North Atlantic Treaty Organization and the United Nations Security Council. Yet, North East Asia never enjoyed a formal, institutionalised collective security structure. As Russia and the United States recede and China emerges in North East Asia, this article questions whether now is the time to consider such an arrangement. Financially, Japan and South Korea are locked into a symbiotic relationship with China (as is the United States), while the government in Beijing continues to militarise and lay territorial and maritime claims to large areas of the region. Moreover, the regime in North Korea, with its new nuclear capabilities, remains unpredictable. Consequently, central components to the question of collective security in North East Asia are the equally vexing questions of what to do about North Korea and whether a new formalised security arrangement would include or exclude the People’s Republic of China.